Social Network Analysis in the History of Sciences : Visualising Sociability in Scientific Expeditions with Gephi - Pereira Antunes, Anderson (2021)
With its origins in Sociology, social network analysis has gained popularity with the development of both Digital Humanities and free network visualization software, such as Gephi. For the History of Sciences, network analysis can highlight how scientific knowledge is socially constructed and dependent on the interactions between individuals and institutions. In this paper, I demonstrate how the analysis and visualization of networks with Gephi can be a valuable tool to understand the sociability of 19th-century scientific expeditions by investigating Louis Agassiz’s and Henry Walter Bates’ travels in Brazil.